Clinical features, treatment and outcome of mucosa-associated lymphoid tissue (MALT) lymphoma of the ocular adnexa: single center experience of 60 patients. - Barbara Kiesewetter (Public Library of Science (PLoS), 2014)
Background Orbital marginal zone B-cell lymphoma (OAML) constitutes for the most frequent diagnosis in orbital lymphoma. Relatively little data, however, have been reported in larger cohorts of patients staged in a uniform way and no therapy standard exists to date. Material and methods We have retrospectively analyzed 60 patients diagnosed and treated at our institution 1999-2012. Median age at diagnosis was 64 years (IQR 51-75) and follow-up time 43 months (IQR 16-92). All patients had undergone uniform extensive staging and histological diagnosis was made by a reference pathologist according to the WHO classification. Results The majority of patients presented with stage IE (n = 40/60, 67%), three had IIE/IIIE and the remaining 17 stage IVE. Seven patients with IVE had bilateral orbital disease whereas the others showed involvement of further organs. Treatment data were available in 58 patients. Local treatment with radiotherapy (14/58, 24%) or surgery (3/58, 5%) resulted in response in 82% of patients. A total of 26 patients (45%) received systemic treatment with a response rate of 85%. Nine patients received antibiotics as initial therapy; response rate was 38%. Watchful-waiting was the initial approach in 6/58 patients. In total 28/58 patients (48%) progressed and were given further therapy. Median time-to-progression in this cohort was 20 months (IQR 9-39). There was no difference in time-to-progression after first-line therapy between the different therapy arms (p = 0.14). Elevated beta-2-microglobulin, plasmacytic differentiation, autoimmune disorder and site of lymphoma were not associated with a higher risk for progress. Conclusion Our data underscore the excellent prognosis of OAML irrespective of initial therapy, as there was no significant difference in time-to-progression and response between local or systemic therapy. In the absence of randomized trials, the least toxic individual approach should be chosen for OAML.